Social Networking of Group Two Innate Lymphoid Cells in Allergy and Asthma - Hurrell, Benjamin P.; Shafiei Jahani, Pedram; Akbari, Omid (Frontiers in Immunology, 2018)
Allergic diseases including asthma, chronic rhinosinusitis and atopic dermatitis are common conditions worldwide. While type 2 immune responses induced by T-cells significantly cause allergic inflammation, the recently identified group two innate lymphoid cells (ILC2s) are emerging as critical players in the development of allergy. Upon allergen exposure, ILC2s are rapidly activated by cytokines released by epithelial cells. Activated ILC2s release various effector cytokines altogether contributing to the pathogenesis of allergy and can even cause inflammation in the absence of T-cells, as observed in asthma. Although the factors inducing ILC2 activation have been identified, evidence suggests that multiple factors can enhance or repress ILC2 proliferation, trafficking or secretion of effector cytokines upon allergic inflammation. In this review, we discuss the recent findings that influence ILC2 activation and the resulting effects on the pathogenesis of allergy. A better understanding of how ILC2s are modulated will open the door to the development of new therapeutic strategies against allergic diseases.